Pengaruh Sistem Penggajian terhadap Efektivitas Pengendalian Internal - Rahmaniar Rahmaniar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
This study aimed to determine the effect of the payroll system on the effectiveness of internal control at PT. TransContinents. The data analysis method in this study uses simple linear regression to predict the effect of the independent variables. The population in this study were all employees of PT. Trans Continent, totaling 93 people. The sampling technique used in this research is saturated sampling, then employees of PT. The Trans Continent samples were employees who had worked for at least two years, namely 40 employees, and were then used as research samples. Of all the research samples, there were 30 banks with 120 research observations, namely 30 banks multiplied by the four years of the research period. The study results show that the payroll system has a positive effect on the effectiveness of internal control. Overall, a sound payroll system can help increase the effectiveness of internal controls within the company by ensuring data accuracy, reducing human error, managing budgets more effectively, and increasing compliance with regulations and policies